2019
DOI: 10.21834/e-bpj.v4i10.1618
|View full text |Cite
|
Sign up to set email alerts
|

Creating Positive Environment for Autism Using Sensory Design

Abstract: The designated learning environment for autism should consider sensory issues to overcome their needs. This paper would review related articles to gain a better understanding of autism needs regarding sensory design, sensory issues, sensory space, internal environment, and physical learning environment. This paper will outline the sensory design of the physical learning environment that would impact by the sensory design towards the physical learning environment. This research paper would be a guide for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 8 publications
1
26
0
1
Order By: Relevance
“…The following component is legibility, and most respondents strongly agreed. Their agreement shows that their knowledge of awareness is in line as discussed by the previous scholar that legibility is a good environment helps to ease of understanding and would be more accessible to autistic children to orientate themselves and identify the activities associated with various rooms (Mcnally et al, 2013;Oi-Zhen et al, 2015;Ghazali, Md Sakip, et al, 2019). The final component for Physical Learning Environment is furniture.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The following component is legibility, and most respondents strongly agreed. Their agreement shows that their knowledge of awareness is in line as discussed by the previous scholar that legibility is a good environment helps to ease of understanding and would be more accessible to autistic children to orientate themselves and identify the activities associated with various rooms (Mcnally et al, 2013;Oi-Zhen et al, 2015;Ghazali, Md Sakip, et al, 2019). The final component for Physical Learning Environment is furniture.…”
Section: Discussionsupporting
confidence: 64%
“…In terms of threshold, most respondents strongly agreed to consider the design. The respondent shows that their knowledge of awareness in line, as discussed by previous scholars, is essential for them to give time, space to prepare for the change and helps with anxieties surrounding sudden sensory change (Ghazali et al, 2019;Love, 2019). This is important because, without the transition space, the shock of going from low stimulus to high stimulus could impact children's performance (Leestma, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Human comfort due to the physical environment affects a child's play behaviour, thus influencing learning (Shaari & Ahmad, 2016). Besides the sensory issues, internal environment, sensory spaces, and the physical learning environment, it is great if the designer would look into the most potential that easily triggers the anxiety among autistic (Ghazali et al, 2019). The aspect of physical learning environment should be highlighted and discussed, such as the building entrance, building scale, safety and security, personal space and movement, wayfinding, legibility, threshold, classroom, quiet room, toilet, visual distraction, sun and glare, lighting, acoustic, smell, calm, low stimulus space, and sensory garden would create positive learning environment (Ghazali et al, 2019).…”
Section: Physical Learning Environmentmentioning
confidence: 99%
“…Besides the sensory issues, internal environment, sensory spaces, and the physical learning environment, it is great if the designer would look into the most potential that easily triggers the anxiety among autistic (Ghazali et al, 2019). The aspect of physical learning environment should be highlighted and discussed, such as the building entrance, building scale, safety and security, personal space and movement, wayfinding, legibility, threshold, classroom, quiet room, toilet, visual distraction, sun and glare, lighting, acoustic, smell, calm, low stimulus space, and sensory garden would create positive learning environment (Ghazali et al, 2019). Research by Che Ahmad & Amirul (2017) highlighted that the physical aspects of the classroom environment's suitability were high for furniture and lighting facilities while the moderate level for air quality, colour, and space.…”
Section: Physical Learning Environmentmentioning
confidence: 99%
“…Early identification and intervention are considered the most effective pathways for supporting and meeting the needs of these children (Pasco, 2018). The physical, social and emotional environments are important areas that need to be adapted to meet their needs (Adamou, et al, 2021;Ghazali, Sakip and Samsuddin, 2019;Li, et al, 2019). However, research has shown that this is not always attainable for many children and families in the general population.…”
Section: Introductionmentioning
confidence: 99%